Implementasi Kebijakan Pendidikan di Era Digital dalam Meningkatkan Kualitas Pembelajaran di MTs Integral Luqman Al-Hakim Bojonegoro - Sofiatul Mukaromah; Sri Minarti (Advances In Education Journal, 2026)
This study discusses the implementation of educational policies in the digital era to improve learning quality at MTs Integral Luqman Al-Hakim Bojonegoro. The research aims to determine the implementation of digital-based educational policies, the use of technology in learning, and their impact on learning quality. This study used a qualitative descriptive method. Data were collected through observation, interviews, and documentation involving teachers and school representatives, especially Mr. Suryadi as the interview source. The results showed that the school had implemented digital learning policies through the use of LCD projectors, PowerPoint, learning videos, Google Classroom, and internet-based learning media. The implementation of digital learning policies improved students’ learning motivation, activeness, and understanding of learning materials. However, several obstacles were found, such as limited facilities, unstable internet networks, and differences in teachers’ digital competencies. Therefore, improving facilities and digital literacy is necessary to optimize learning quality in the digital era.